Electronic Assessment System Transforms Schools: Could something as simple as implementing an electronic assessment system increase rigor, improve students' behavior, and develop their moral character? See what happened in one district. Issue 4 (April 2015) - Sailler, Robert
In this satirical article, the author discusses the impact of electronic assessment systems on a school, ranging from academic rigor to students' behavior.